UJI RHODAMIN B PADA LIP CREAM YANG BEREDAR DI TOKO KOSMETIK KOTA KUDUS MENGGUNAKAN KROMATOGRAFI LAPIS TIPIS - Safira Ramandani; Endang Setyowati; Muhammad Khudzaifi (Yayasan Nusantara Hasana Berdikari, 2025)
Cosmetic products, including lipstick, are products that require coloring agents, usually in the form of lip cream preparations. One of the dangerous coloring agents circulating in the market is Rhodamine B. Rhodamine B is a dangerous synthetic dye that is carcinogenic. The purpose of this study was to identify the presence of Rhodamine B in lip creams circulating in Kudus City. The research method was carried out quantitatively because it determined the levels of Rhodamine B using Thin Layer Chromatography (TLC). The lip cream samples studied were 5 samples with different brands and sold at the Kudus City Cosmetics Store. Rhodamine B identification test on lip cream by observing the number of Retention Factor (Rf) values, visual stain color, and fluorescence color under UV light 254 nm and 366 nm. The identification results of the five samples tested contained two samples suspected of containing synthetic rhodamine B dye, namely samples A and E, this can be seen from the color of the spots seen visually are pink and orange, while under UV light it is purple and fluoresces yellow. For the Rf value of rhodamine B of 0.68, it is the same as sample A, while samples B, C, D, and E have a value of 0.7. The conclusion of this study is that the five lip cream samples with different brands contain Rhodamine B, namely in sample A and E.